2020
DOI: 10.1371/journal.pcbi.1007751
|View full text |Cite
|
Sign up to set email alerts
|

A molecular odorant transduction model and the complexity of spatio-temporal encoding in the Drosophila antenna

Abstract: Over the past two decades, substantial amount of work has been conducted to characterize different odorant receptors, neuroanatomy and odorant response properties of the early olfactory system of Drosophila melanogaster. Yet many odorant receptors remain only partially characterized, and the odorant transduction process and the axon hillock spiking mechanism of the olfactory sensory neurons (OSNs) have yet to be fully determined. Identity and concentration, two key characteristics of the space of odorants, are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(87 citation statements)
references
References 51 publications
(97 reference statements)
3
84
0
Order By: Relevance
“…series of input pulses which durations and inter-stimulus-intervals were drawn from a Gaussian distribution. We found that our model reproduces the data to a similar quality (relative error of around 6%) as previous linear-nonlinear models (Kim et al, 2011(Kim et al, , 2015Martelli et al, 2013;Nagel and Wilson, 2011;Lazar and Yeh, 2020), even though it has fewer free parameters (see Figure 3).…”
Section: Constraining the Orn Model To Biophysical Evidencesupporting
confidence: 71%
See 2 more Smart Citations
“…series of input pulses which durations and inter-stimulus-intervals were drawn from a Gaussian distribution. We found that our model reproduces the data to a similar quality (relative error of around 6%) as previous linear-nonlinear models (Kim et al, 2011(Kim et al, , 2015Martelli et al, 2013;Nagel and Wilson, 2011;Lazar and Yeh, 2020), even though it has fewer free parameters (see Figure 3).…”
Section: Constraining the Orn Model To Biophysical Evidencesupporting
confidence: 71%
“…in line with previous experimental and theoretical studies (Kim et al, 2011(Kim et al, , 2015Martelli et al, 2013;Lazar and Yeh, 2020). We simulated pairs of ORNs expressing different OR types, as they are co-housed in sensilla.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…• Changing the affinity values of each of the odorant-receptor pairs characterizing the input of the Odorant Transduction Process [37],…”
Section: Eoscircuits Library For Larva and Adult Early Olfactory Circmentioning
confidence: 99%
“…• Changing parameter values of the Biological Spike Generators (BSGs) associated with each OSN [37],…”
Section: Eoscircuits Library For Larva and Adult Early Olfactory Circmentioning
confidence: 99%